2005
DOI: 10.1001/archpsyc.62.8.841
|View full text |Cite
|
Sign up to set email alerts
|

Family History of Psychiatric Illness as a Risk Factor for Schizoaffective Disorder

Abstract: Schizoaffective disorder is not simply a subgroup of either bipolar disorder or schizophrenia but may be genetically linked to both, with schizoaffective disorder being a subtype of each or a genetic intermediate form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
79
2
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(93 citation statements)
references
References 23 publications
9
79
2
3
Order By: Relevance
“…The risk magnitudes in offspring were in line with earlier publications on familial psychotic disorders and schizophrenia (Albus and Maier, 1995;Cannon et al, 1998;Cardno et al, 1999;Kendler and MacLean, 1990;Laursen et al, 2005;Shih et al, 2004). The present study adds further knowledge to previous research because of its approach; it was based on all hospitalized cases in Sweden between 1987 and 2004, which yielded 21,199 male and 19,029 female cases of psychotic disorders in addition to 12,799 paternal and 23,021 maternal cases of psychotic disorders (including schizophrenia).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The risk magnitudes in offspring were in line with earlier publications on familial psychotic disorders and schizophrenia (Albus and Maier, 1995;Cannon et al, 1998;Cardno et al, 1999;Kendler and MacLean, 1990;Laursen et al, 2005;Shih et al, 2004). The present study adds further knowledge to previous research because of its approach; it was based on all hospitalized cases in Sweden between 1987 and 2004, which yielded 21,199 male and 19,029 female cases of psychotic disorders in addition to 12,799 paternal and 23,021 maternal cases of psychotic disorders (including schizophrenia).…”
Section: Discussionsupporting
confidence: 86%
“…These findings have not been reported consistently (Maier et al, 1993;Sham et al, 1994). The influence of genetic factors has been reported to have a significantly higher effect in women than men in some studies (Maier et al, 1993) but not in others (Albus and Maier, 1995;Cannon et al, 1998;Laursen et al, 2005). Consequently, there is a need for further research into the genetic etiology of psychotic disorders and schizophrenia with specific attention paid to age and sex effects.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…They are clearly incompatible with the argument that schizoaffective disorder is a variant of bipolar disorder 5, 48, 49. Nor are they easy to reconcile with the longstanding—and currently highly topical—proposal that schizoaffective disorder represents the midpoint along a continuum of psychosis, as conceptualized either genetically 6, 13, clinically 8, 50, 51, or both 52. This would predict less volume change in schizoaffective disorder than in schizophrenia, something that none of the analyses carried out in this study supported.…”
Section: Discussionmentioning
confidence: 96%
“…Clinical studies have performed little to clarify the status of the disorder, finding that it does not clearly separate from schizophrenia or bipolar disorder, either cross‐sectionally 8, 9, or in terms of its course and outcome (for a review, see 10). Similarly, family history studies have found high rates of affective disorders in the first‐degree relatives of patients with schizoaffective disorder, but also elevated rates of schizophrenia 11, 12, 13, 14.…”
Section: Introductionmentioning
confidence: 91%